An Analysis of Factors Influencing Customer Creditworthiness in the Banking Sector of Kingdom of Bahrain - Maryam Ismail Ebrahim (International Journal of Engineering and Management Research, 2019)
This research is based on Bahraini bankers’ perception on the factors influencing customer creditworthiness in the banking sector of Kingdom of Bahrain. We consider that the research was done in the Kingdom of Bahrain which has a growing banking industry. To enhance the whole procedure of the creditworthiness, it is vital for an employer to understand the most important factors influencing customer creditworthiness. The purpose of the study was to investigate the factors influencing customers creditworthiness in the banking industry. The creditworthiness can be assessed through qualitative factors, quantitative factors and risk factors. The research was conducted through a survey, using the questionnaire as the research instrument. The respondents of the study are employees of banks across the Kingdom dealing with creditworthiness. The statistical tools used in the study are Multiple Regression Analyses and weighted mean. The researcher has found that there is significant relationship between all three factors and creditworthiness, and they don’t equally influence the creditworthiness. The research provides recommendations to banks in assessing the creditworthiness. The researcher recommended that employees must use the most effective methods such as credit scoring to conduct the analysis of creditworthiness in order to make effective decisions. Moreover, the researcher recommended that analysts should take into considerations the most effective factors in the analysis process and they must not neglect other.